The Screening of Black Point in Commercial Bread Wheat Cultivars Grown in Turkey, and The Effect of Black Point on Thousand Grain Weight - Sesiz, Uğur (My University, 2023)
The black point is a discoloration that shows up on the embryos of wheat and barley, and it is becoming an important problem in many wheat-growing areas. In this study, 200 commercially important bread wheat varieties that were cultivated between 1931 and 2017 in Turkey were screened in terms of black point, and the effect of black point was observed on thousand grain weight in all cultivars. The trials were conducted in accordance with the augmented block trial design in three environments during the 2016-17 growing season. A high variation was observed among the cultivars for black point and thousand grain weight. Twelve varieties (6% of populations) showed no discoloration (0.00%) in any environment, whereas 44 varieties (22% of population) showed discoloration rate more than 10.00%. The first three most susceptible cultivars showed black point percentages of 38.76, 32.08, and 27.5, respectively. In the remaining cultivars, eighty-eight showed discolorations up to 5.00%, whereas the rest demonstrated discoloration from 5.00% to 24.00%. Interestingly, a positive correlation was observed between black point damage and thousand grain weight (r=0.32). The reasonable interpretation is that the larger seed surfaces may have increased the effect of black point causes, such as pathogens and oxidative reactions. This screening enabled us to determine black point susceptible and tolerant cultivars in well-known bread wheat cultivars growing in Turkey. Hence, the results will be useful for wheat production and wheat breeding approaches in Turkey and around the world.
Keywords: Triticum aestivum; Bread wheat; Black point; Thousand grain weight